The impact of AI as a mediator on effective communication: enhancing interaction in the digital age - Ateeq, Ali; Milhem, Marwan; Alzoraiki, Mohammed; Dawwas, Mohammed I. F.; Ali, Shafeeq Ahmed; Yahia Al Astal, Ahmad (Frontiers in Human Dynamics, 2024)
This research examines the impact of methods of communication and artificial intelligence on the effectiveness of communication in small and medium-sized enterprises (SMEs) in Bahrain. A quantitative research approach was used to gather data from 211 employees using structured questionnaires. The study used convenience sampling and deployed SmartPLS4 for Partial Least Squares Structural Equation Modeling (PLS-SEM) and SPSS for descriptive statistics analysis. The study examined the impact of different communication strategies (conventional vs. AI-assisted) on communication efficacy. AI was included as a mediating variable in this analysis. The results indicate that communication methods have a substantial impact on AI (β = 0.725, T-value = 27.612, p-value = 0.000) and communication effectiveness (β = 0.439, T-value = 9.150, p-value = 0.000). Artificial intelligence (AI) has a role in connecting methods of communication and effectiveness of communication, acting as a mediator with an indirect impact of 0.286. The mediation effect indicates that AI amplifies the influence of communication methods on effectiveness. The study’s findings indicate that the combination of AI with strong communication methods greatly improves the effectiveness of communication. Practical consequences include the need for firms to allocate resources toward well-designed methods of communication, ongoing staff education, and the smooth incorporation of artificial intelligence capabilities. Further investigation is needed to examine other settings and additional elements that influence and support these results, in order to confirm and broaden the scope of this study.